The Papacy in the Modern World : a Political History. - Coppa, Frank J. (Reaktion Books, 2014)
Describing the triumphs, controversies and failures of popes over the past 200 years - including Pius IX, who was criticized for his campaign against Italian unification and his proclamation of papal infallibilty, and Pius XII, denounced for his 'silence' during the Holocaust and 'impartiality' during the Second World War - this book offers a comprehensive and enlightening view of the papal state. Examining a wide variety of source, some only recently made available by the Vatican archives, The Papacy in the Modern World sheds new light on this institution and offers valuable insights into events previously shrouded in mystery.